P604 Infection Risk in Elderly Patients with Inflammatory Bowel Disease under anti-TNF, ustekinumab or vedolizumab biologic therapies: A Prospective Multicenter observational One-Year follow-up comparative study. (21st January 2022) - Bozon, A; Serrero, M; Caillo, L; Gilletta, C; Benezech, A; Nancey, S; Combes, R; Danan, G; Akouete, S; Pages, L; Bourgaux, J F; Boivineau, L; et al.
Abstract: Background: The emergence of biologics has significantly improved the course of inflammatory bowel diseases (IBD) despite a potential higher risk of infections. Use of biologics in the elderly population remains a challenge since elderly patients are at higher risk of infection. Anti-tumor necrosis factor (anti-TNF), vedolizumab and ustekinumab are all potentially susceptible to increase the risk of infection. We conducted a one-year, prospective, multicenter, observational study comparing the respective infectious risk under anti-TNF, vedolizumab or ustekinumab in elderly patients with IBD. Methods: All IBD patients over 65 years, from six medical centers and receiving anti-TNF (first group), vedolizumab or ustekinumab (second group, defined as new biologics) treatment were included. The primary endpoint was the prevalence of at least one infection during follow-up. The cumulative risk of severe infection requiring hospitalization was recorded. Results: The study included 207 consecutive patients, 113 under anti-TNF and 94 patients under vedolizumab or ustekinumab (median age 71 years, 112 with Crohn's disease and 95 with ulcerative colitis). There was no difference concerning combination therapy, steroids use and the Charlson index between the two groups. The prevalence of infections was similar in patients under anti-TNF (29%) and in those under vedolizumab and ustekinumab (28%) (p=0.81). There was no difference in terms of type of infection, infection-related hospitalization (7% vs 6.4%), antibiotic prescription and treatment efficacy between the two groups. In patients over 75 years of age (n=50), the prevalence of infections was comparable in both groups. Conclusion: Around 30 % of elderly patients with IBD under biologics experienced at least one infection during the one-year study period. The risk does not differ between patients treated with anti-TNF and those under vedolizumab or ustekinumab.